Advancing Islamic Education in the Bangsamoro Region: The Recognized Islamic Higher Education Institution - Rakim Sammy; Abdul Lantong (Cendekia: Kependidikan dan Kemasyarakatan, 2026)
Islamic education in the Philippines struggled to modernize due to its strong emphasis on religious knowledge. The new Bangsamoro autonomy has renewed hopes to strengthen Islamic education through the establishment of the Bangsamoro Kulliyyah for Islamic Studies (BKIS). Through a qualitative case study approach, this study explores BKIS's evolving role in advancing Islamic education and how Indonesia's intervention has shaped its institutional direction. Data gathered through guided interviews with key stakeholders, FGDs with faculty and students, and document analysis of curricula, MoUs, and policies. Thematic analysis and data triangulation confirm that BKIS plays a transformative role in reforming BARMM's Islamic education alongside Indonesia's transnational contribution, providing significant support. However, the success of this cooperation hinges on the contextual adaptation of foreign models, the building of local capacity, and the political will to sustain reforms. BKIS thus represents both an innovation hub and a symbol of Bangsamoro identity, bridging global influences with local needs. BKIS served as a testament to the Bangsamoro's continuous efforts to advance Islamic education. This study contributes to the development of Islamic education, particularly in Islamic higher education.